Study Abroad and Service Learning Assisting Students in Learning Croatian Language - Mikelić Preradović, Nives (Array, 2012)
The goal of this paper is to connect the framework of the interactive multimedia project AFILC (Assisting Foreigners in Learning Croatian) with the study abroad and service learning experience of exchange students in the University of Zagreb. The purpose of the AFILC is to develop language learning materials that will motivate foreign students to learn the Croatian language at their own pace and help them cope with its grammatical richness. The purpose of the international service learning course is to motivate exchange students to deeply experience Croatian language and culture and to get insight into the relevance of their service experiences to their personal, career, educational and civic goals.